2020
DOI: 10.1016/j.cnsns.2019.105033
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of escape and transition dynamics in the presence of dissipative and gyroscopic forces in two degree of freedom systems

Abstract: Escape from a potential well can occur in different physical systems, such as capsize of ships, resonance transitions in celestial mechanics, and dynamic snap-through of arches and shells, as well as molecular reconfigurations in chemical reactions. The criteria and routes of escape in one-degree of freedom systems has been well studied theoretically with reasonable agreement with experiment. The trajectory can only transit from the hilltop of the one-dimensional potential energy surface. The situation becomes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 79 publications
(217 reference statements)
0
22
0
Order By: Relevance
“…As a result, the above relations together define a cone at the position (X 0 1 , X 0 2 , X 0 3 ) within the tube of transition. Here we refer to it as the cone of velocity, in analogy with the wedge of velocity discussed by Conley [36] (see also [11]). Notice the cone only exists inside of the tube of transition to ensure R > 0.…”
Section: Trajectories In the Position Spacementioning
confidence: 99%
See 3 more Smart Citations
“…As a result, the above relations together define a cone at the position (X 0 1 , X 0 2 , X 0 3 ) within the tube of transition. Here we refer to it as the cone of velocity, in analogy with the wedge of velocity discussed by Conley [36] (see also [11]). Notice the cone only exists inside of the tube of transition to ensure R > 0.…”
Section: Trajectories In the Position Spacementioning
confidence: 99%
“…For conservative systems with higher degrees of freedom, the transition boundary for all possible escape trajectories is known to be the stable and unstable invariant manifolds of a normally hyperbolic invariant manifold (NHIM) [10] of a given energy. Recently, it was found that the corresponding transition boundary for dissipative systems is the stable invariant manifolds of an index-1 saddle connecting the potential wells [11,12]. Specifically, for an intermediate case of two degree of freedom, the NHIM is a collection of periodic orbits around the index-1 saddle, each periodic orbit corresponding to a given energy [13,4,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deterministic evolution of a system between two stable states through an intermediate unstable state is a fundamental setting for an important form of dynamical evolution that informs our way of thinking of "transition phenomena". This dynamical situation is common to many diverse fields in science and engineering, such as celestial mechanics [1,2], structural mechanics [3][4][5], and chemical reaction dynamics. This setting is natural for studies in the latter area and will be the focus of the applications that we consider.…”
Section: Introductionmentioning
confidence: 99%